2002
DOI: 10.1179/oeh.2002.8.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pesticide Applications on Respiratory Health of Ethiopian Farm Workers

Abstract: The effects of pesticide use on the respiratory health of agricultural farm workers were studied in 203 farm workers and 131 controls. The farm workers were sprayers, supervisors, technicians, and pest assessors. Pulmonary function was found to be remarkably poor among the non-smoker supervisors, followed by the non-smoker sprayers, as compared with that of the non-smoker controls. The means (SD) of FVC and FEV1 for supervisors and sprayers were 2.88 (0.41), 3.05(0.50) and 2.74(0.38), 2.89(0.54), respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…Alternatively, the direct effects of the pesticides on the alveolar-capillary membrane via peripheral muscarinic receptors in the airways and nicotinic receptors in respiratory muscles can also be envisaged. Studies in laboratory animals have demonstrated epithelial hyperplasia, thickening of the alveolar capillary membrane, degeneration of alveoli 7,31,32) and neuromuscular changes in respiratory muscles 33) leading to impairment of lung function following exposure to OP aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the direct effects of the pesticides on the alveolar-capillary membrane via peripheral muscarinic receptors in the airways and nicotinic receptors in respiratory muscles can also be envisaged. Studies in laboratory animals have demonstrated epithelial hyperplasia, thickening of the alveolar capillary membrane, degeneration of alveoli 7,31,32) and neuromuscular changes in respiratory muscles 33) leading to impairment of lung function following exposure to OP aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…13 While spraying the pesticide, the use of personal protective devices (PPDs) could reduce its direct contact with the skin and inhalation of pesticides, thereby potentially reducing the acute and chronic health hazards to the sprayers. 11 Only 44.5% (78/175) of the farmers have been wearing appropriate PPDs such as safety shoes, respirator, gloves, goggles, and hat. However, it has been reported that nearly 22.2% (39/175) of them have never worn any PPDs and 33.1% (58/175) have been applying the pesticides with their usual wear.…”
Section: Commentmentioning
confidence: 99%
“…Two of them have shown that exposure to low levels of OP insecticides led to airway narrowing and decreased expiratory flow rate and volumes in sprayers showing decreased acetylcholinesterase (AChE) levels (Kesavachandran et al, 2006;Peiris-John et al, 2005). A higher prevalence of respiratory symptoms supported by reduced lung function test has been associated with occupational exposure to pesticides (Kossman et al, 1997;Bener et al, 1999;Mekonnen & Agonafir, 2002 and household exposure to insecticide sprays (Newton & Breslin, 1983). By contrast, contradictory studies showing no adverse lung effects after long-term spraying of either paraquat (Senanayake et al, 1993) or OPs (Ngowi et al, 2001) have also been reported.…”
mentioning
confidence: 96%